PERBEDAAN KARAKTERISTIK PASIEN CHF (CHRONIC HEART FAILURE) PADA USIA DEWASA DAN USIA LANJUT SERTA HUBUNGANNYA DENGAN KEMATIAN SELAMA PERAWATAN - WIRDANI FADHILA; AHMAD HANDAYANI (LP2MTBM MAKARIOZ, 2022)
The heart is the most important organ in the human body, which has the main function of pumping blood throughout the body. If there is an abnormality in one of the components of the heart, it will cause a disturbance in the process of pumping blood by the heart, causing failure to pump blood. Heart failure is a condition in which the heart is unable to pump sufficient blood for the body's needs. Congestive heart failure is failure of the right and left heart. Where the data source is obtained from MEDLINE, Google scholar, PubMed and Google. Journals with cross sectional, before after study and observational study methods were included in this literature study. The criteria for respondents in this literature review are adult and elderly patients diagnosed with heart failure. The results of this study are in accordance with the theories that have been stated that the most common cause of congestive heart failure in the elderly (> 60 years) with the most frequent sex is women who are caused by a decrease in the hormone estrogen which triggers the formation of atherosclerosis, with different comorbid factors. in each patient, namely, anemia caused by chronic disease, hypertension that triggers the thickening of the heart wall, diabetes mellitus, depression, and psychological stress.